2017
DOI: 10.5539/ies.v10n9p1
|View full text |Cite
|
Sign up to set email alerts
|

A Language Teacher’s Reflection on Maladaptive Immunity, Possible Selves and Motivation

Abstract: The concept of language teacher immunity as productive and maladaptive system has emerged in very recent years, although motivation has been incrementally studied in second language field. It is important to establish a relationship between language teacher immunity, possible selves and motivation. This study aimed to focus on a teacher's conception and views of adaptive skill, self and motivation while dealing with problems in a certain foreign language classroom environment. The case study was idiographic, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In addition, the Ministry of Education, English language teaching departments, and textbook authors must work to reformulate reading text problems so that second and foreign language learners may gain more abstract and productive abilities. Teachers of the English as a Foreign Language (EFL) are able to question themselves about EFL texts (Ordem, 2017c). Adding integrated assignments to reading materials continues to be a significant concern for EFL textbook authors.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the Ministry of Education, English language teaching departments, and textbook authors must work to reformulate reading text problems so that second and foreign language learners may gain more abstract and productive abilities. Teachers of the English as a Foreign Language (EFL) are able to question themselves about EFL texts (Ordem, 2017c). Adding integrated assignments to reading materials continues to be a significant concern for EFL textbook authors.…”
Section: Discussionmentioning
confidence: 99%
“…In line with these effects, they claimed that teachers could develop two types of immunity: productive immunity or maladaptive immunity. Ordem (2017), in a case study, dwelled upon the teacher's ideas and attitudes toward adaptive skill, self, and motivation. The findings revealed that through reflection on their previous experiences, teachers presented maladaptive behaviours.…”
Section: Language Teacher Immunitymentioning
confidence: 99%